6(2t-6)+5t=36-t

Simple and best practice solution for 6(2t-6)+5t=36-t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2t-6)+5t=36-t equation:


Simplifying
6(2t + -6) + 5t = 36 + -1t

Reorder the terms:
6(-6 + 2t) + 5t = 36 + -1t
(-6 * 6 + 2t * 6) + 5t = 36 + -1t
(-36 + 12t) + 5t = 36 + -1t

Combine like terms: 12t + 5t = 17t
-36 + 17t = 36 + -1t

Solving
-36 + 17t = 36 + -1t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add 't' to each side of the equation.
-36 + 17t + t = 36 + -1t + t

Combine like terms: 17t + t = 18t
-36 + 18t = 36 + -1t + t

Combine like terms: -1t + t = 0
-36 + 18t = 36 + 0
-36 + 18t = 36

Add '36' to each side of the equation.
-36 + 36 + 18t = 36 + 36

Combine like terms: -36 + 36 = 0
0 + 18t = 36 + 36
18t = 36 + 36

Combine like terms: 36 + 36 = 72
18t = 72

Divide each side by '18'.
t = 4

Simplifying
t = 4

See similar equations:

| (2/3)z=4.5 | | 18x^3=15x | | 36x^2-8x-5=0 | | 3v-9=51 | | 7000=mx+b | | 4x^2-30x+14= | | 39x-237=0 | | 2=3x+b | | -8x+29=-36 | | 2x-61=689 | | 1=5(4x+1)+21x | | 1100=d+3w | | 6(4.8)= | | -3z-27=39 | | -12x-6x=-7 | | 2x+35=-22 | | 4x=(360/6) | | 2x+65=635 | | 3(5i-2)+2=36 | | 2x*2=15 | | 2x(3)=416 | | -5x-25=80 | | (8r-7)(r+7)-(3r-1)(r+7)= | | 2x^2+100x+3600=0 | | 2x+25=50 | | 29-4.50x=42.50 | | 7x+5=5+2x+35 | | 5x^2+6x+3= | | 29-4.50x=52.5 | | A+8=2a-58 | | 6(g-2)+g=8g-20 | | 4x^2-17x+30=8x+5 |

Equations solver categories